The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.bjid.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Clostridium difficile: a hospital-based descriptive study in Argentina and Mexico

Abstract: A prospective study was conducted in four tertiary hospitals in Argentina and Mexico in order to describe the occurrence of Clostridium difficile infection (CDI) in these settings. The objective was to evaluate the incidence of CDI in at-risk populations in Argentina (one center) and Mexico (three centers) and to further explore potential study sites for vaccine development in this region. A prospective, descriptive, CDI surveillance study was conducted among hospitalized patients aged ≥40 years who had receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
1
19
0
4
Order By: Relevance
“…In addition to healthcare-acquired CDI, community-acquired CDI is increasingly a concern as rates increase [ 5 7 ]. Though lower in incidence than in the USA, CDI remains a large and growing concern in both Europe and Asia; however, published estimates may undercount the actual burden given the lack of testing, underdiagnoses, and potentially missed community-acquired cases [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to healthcare-acquired CDI, community-acquired CDI is increasingly a concern as rates increase [ 5 7 ]. Though lower in incidence than in the USA, CDI remains a large and growing concern in both Europe and Asia; however, published estimates may undercount the actual burden given the lack of testing, underdiagnoses, and potentially missed community-acquired cases [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, el uso de antimicrobianos al menos con 14 días de antelación y hasta 3 meses es uno de los factores comunes en el 100% de los pacientes sintomáticos (Cohen, Gerding, and Johnson 2010). Aunque en teoría cualquier antibiótico puede ser relacionado con la enfermedad, medicamentos como la clindamicina y las cefalosporinas identificadas en proporción de uso de 33 y 60% respectivamente explican en parte las tasas de prevalencia para las EACD en los hospitales en estudio al igual que lo reportado por otros investigadores (Amy et al 2015;Lopardo et al 2015).…”
Section: Discussionunclassified
“…En conclusión, C. difficile es una bacteria que se encuentra INTRODUCCIÓN C. difficile es una bacteria Gram positiva anaerobia, productora de esporas responsable de un porcentaje importante de diarrea asociada al uso de antibióticos de amplio espectro en el ámbito hospitalario. Fue identificado en 1935 como Bacillus difficilis en la flora fecal de niños sanos y reconocido como causa de la colitis asociada a antibióticos (Lopardo et al 2015;Price, Larson, and Crow 1979).…”
Section: Introductionunclassified
“…The 017 strain was shown to have a particularly high prevalence in a study in Argentina, in which the percentage of CDI cases attributable to this strain was above 75% from 2002 to 2006 in an urban tertiary hospital (31). In the 2015 study of CDI in 4 tertiary hospitals in Argentina and Mexico by Lopardo et al (22), the predominant strain type recovered was also ribotype 017.…”
Section: Difficile Strain Distributions Vary In Resource-limited Smentioning
confidence: 94%
“…A 2017 study in three hospitals in Colombia utilizing detection of toxins A/B (by EIA) in stools from patients with diarrhea estimated the CDI prevalence rate at 9.7% (21). In contrast, a 2015 descriptive CDI surveillance study in 4 tertiary hospitals in Argentina and Mexico used ELISA for toxins A and B to test stools from hospitalized patients aged Ն40 years who developed diarrhea within 30 days after receiving in-hospital antibiotics and found that 41% of patients with diarrhea tested positive for toxinogenic C. difficile (22). Similarly García et al (23), working in a Peruvian tertiary care setting and utilizing an EIA for toxins A/B, showed that CDI was the cause of 35.2% of cases of nosocomial diarrhea.…”
Section: When You Look For CDI You Find It In Rates That Are Similamentioning
confidence: 99%